2021
DOI: 10.1002/tox.23141
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐ovo permethrin exposure affects growth, brain morphology and cardiac development in quail

Abstract: Permethrin is a commonly used, highly effective pesticide in poultry agriculture, and has recently been trialed in conservation efforts to protect Galápagos finch hatchlings from an invasive ectoparasite. Although permethrin is considered safe for adults, pesticides can have health consequences when animals are exposed during early life stages. The few studies that have examined permethrin's effects in embryonic chicks and rats have shown hydrocephaly, anencephaly, reduced cellular energy conversion, and disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(128 reference statements)
0
6
0
Order By: Relevance
“…[72][73][74] Furthermore, there were only a few studies about the exposure of pyrethroid induced the change of brain morphology. 75,76 According to report, in mouse cells, DLM can continuously increase the content of Ca 2+ in cells, and the imbalance of Ca 2+ homeostasis will promote ER stress. 77 The response of ER stress will produce a large amount of CHOP, which inhibits the expression of Bcl-2 located on the mitochondrial membrane, thereby promoting apoptosis of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[72][73][74] Furthermore, there were only a few studies about the exposure of pyrethroid induced the change of brain morphology. 75,76 According to report, in mouse cells, DLM can continuously increase the content of Ca 2+ in cells, and the imbalance of Ca 2+ homeostasis will promote ER stress. 77 The response of ER stress will produce a large amount of CHOP, which inhibits the expression of Bcl-2 located on the mitochondrial membrane, thereby promoting apoptosis of the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effects of DLM neurotoxic have been reported in mammals, fish, and insects 72–74 . Furthermore, there were only a few studies about the exposure of pyrethroid induced the change of brain morphology 75,76 . According to report, in mouse cells, DLM can continuously increase the content of Ca 2+ in cells, and the imbalance of Ca 2+ homeostasis will promote ER stress 77 .…”
Section: Discussionmentioning
confidence: 99%
“…Perm, due to its lipophilic properties, accumulates in tissues with high lipid content such as liver, kidney and breast, as well as fat and nervous system, and is metabolized in the liver and excreted through the kidneys (Ding et al, 2013). Experimental studies have shown that Perm adversely affects the peripheral and central nervous system in mammals, causes neurotoxic effects by inducing oxidative stress in the neonatal rat brain, increases malondialdehyde levels by causing lipid peroxidation, has advers effects on the liver and endocrine system, and causes degenerative and necrotic damage in the kidney, increases apoptotic cell death, decreases sperm concentration in rats, and causes heart diseases (Wang et al, 2016;Romero et al, 2017;Curtis et al, 2021). These undesirable effects of Perm can cause fetal toxicity and developmental delay in offspring, especially during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…We presented an extensive review on the toxic effects of pyrethroids at multiple levels (Ravula & Yenugu, 2021c). Recent studies report that bifenthrin causes reduction in pregnancy potential and defects in fetal growth and development (Curtis et al, 2021; Park et al, 2021). Malformation of male gamates, DNA damage and epimutations in sperm and reproductive toxicity were evident in animal models that were exposed to fenvalerate, cypermethrin, permethrin, deltamethrin and fenpropathrin, respectively (Abu Zeid et al, 2021; Ha et al, 2021; Hozyen et al, 2020; Huang et al, 2021; Thorson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%